1998
DOI: 10.1177/106342669800600104
|View full text |Cite
|
Sign up to set email alerts
|

Troubled or Troubling? Characteristics of Youth Referred to a System of Care Without System-Level Referral Constraints

Abstract: The characteristics of 128 youth with emotional and behavioral disorders referred to a system of care were investigated according to agency referral, behavioral and emotional issues, and risk factors. The referral process in this system of care was unique, with each agency referring youth deemed to need multiagency services. The primary analysis used a two-step clustering procedure to examine characteristic profiles, and results produced evidence of four types of referral profiles: Troubled, Troubling. Trouble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Alternatively, this result could be interpreted as teachers not being sufficiently concerned about moderate male externalizing problems. Given that previous studies have found a strong association of externalizing problems with poor educational outcomes (Breslau, Miller, Chung, & Schweitzer, 2011; McLeod, Uemura, & Rohrman, 2012; Porche, Costello, & Rosen-Reynoso, 2016), the finding here that moderate male externalizing problems are rated as less severe than moderate female internalizing problems might be an indication that teachers are more likely to interpret male externalizing symptoms as signs of “troubling” rather than “troubled” behavior that should be interpreted as concerning (Rosenblatt et al, 1998).…”
Section: Discussionmentioning
confidence: 52%
“…Alternatively, this result could be interpreted as teachers not being sufficiently concerned about moderate male externalizing problems. Given that previous studies have found a strong association of externalizing problems with poor educational outcomes (Breslau, Miller, Chung, & Schweitzer, 2011; McLeod, Uemura, & Rohrman, 2012; Porche, Costello, & Rosen-Reynoso, 2016), the finding here that moderate male externalizing problems are rated as less severe than moderate female internalizing problems might be an indication that teachers are more likely to interpret male externalizing symptoms as signs of “troubling” rather than “troubled” behavior that should be interpreted as concerning (Rosenblatt et al, 1998).…”
Section: Discussionmentioning
confidence: 52%
“…Importantly, our measures of peer violence were quite severe, including serious physical assault and gun displays. The lack of association could be due to the fact that violence has become somewhat normalized in urban areas, or that students involved in peer violence are sometimes viewed as “troubling” rather than “troubled,” and are less likely to be referred for mental health services . By contrast, the finding that victims of sexual assault receive services is encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…Profi les may ultimately prove to be benefi cial in the creation of specifi c, targeted intervention programs (Dembo & Schmeidler, 2003). Previous studies using clustering procedures have sought to determine profi les across subtypes of disabilities, including learning disabilities (Satz & Morris, 1981), oral language impairments (Speece, Roth, Cooper, & De La Paz, 1999), social withdrawal (Harrist, Zaia, Bates, Dodge, & Pettit, 1997), and behavioral disorders (Cullinan, Epstein, & Quinn, 1996;Rosenblatt, et al, 1998). Moreover, clustering procedures have been used with children presenting academic and behavioral problems, including youth delinquency (Dembo & Schmeidler, 2003), children at-risk for school failure (Speece & Cooper, 1990), and antisocial preadolescents (Pevalin, Wade, & Brannigan, 2003).…”
Section: Cluster Analysis and Examination Of Riskmentioning
confidence: 99%
“…Behavioral, emotional, family, and child risk factors were examined across 128 youth to determine the heterogeneity of referral profi les. Four clusters, presenting distinct levels of risk across risk factors, were identifi ed; children in the most severe risk category had elevated risks across home and school settings, as well as across child and family variables (Rosenblatt et al, 1998). Finally, Speece and Cooper (1990) assessed profi les of risk in 112 fi rst-grade children, 63 of whom were identifi ed as at risk of school failure.…”
Section: Cluster Analysis and Examination Of Riskmentioning
confidence: 99%